(untitled) (Research, Society and Development, 2021)
Hylocereus lemairei (Hook.) is a plant popularly known as pitaya-purple, whose fruits are known as dragon fruit. This paper aimed to carry out the physical-chemical and chemical characterization of fermented beverages based on H. lemairei fruits. Fermented beverages were elaborated using two different commercial yeasts of Saccharomyces cerevisiae [Biolievito Bayanus (BB) and Arom Cuvée (AC)] and were characterized by NMR. In addition, the antioxidant capacity (DPPH and ABTS) and Total Phenolic Content (TPC) based on the Folin Ciocalteu method were determined. According to the legislation, the fermented beverages from BB and AC showed alcoholic levels of 12.9 and 12.5% (v/v) and pH of 3.9 and 3.8, respectively. The chemical compounds of both beverages were similar, whose major organic compounds are glycerol, myo-inositol, tyrosol, and citric and succinic acids. According to the DPPH and TPC evaluation, BB beverage (248.3 µM TE and 117.6 mg GAE L-1) presented higher antioxidant capacity when compared to the BC beverage (219.8 µM TE and 108.4 mg GAE L-1). In the ABTS assay, both beverages were not statistically different (p < 0.05). Tyrosol may be responsible for increasing the antioxidant capacity and phenolic compounds content when compared to the control juice used to prepare fermented beverages.